Problematika Pemberian Tugas Matematika Dalam Pembelajaran Daring - Rangkuti, Cirvy Jani Saputri; Sukmawarti, Sukmawarti (Indonesian Research Journal on Education, 2022)
Large-scale social restrictions caused by the spread of COVID-19 have resulted in changes in the implementation of mathematics learning. Mathematics learning cannot be carried out directly in schools. On the contrary, mathematics learning activities must be carried out at home (Learning from home). Mathematics teachers are required to carry out online learning so that mathematics material can be mastered by students completely. Obstacles such as the inhibition of the internet network, the limited use of cellphones, and the high cost of internet data quotas are problematic and the dilemmas faced in giving mathematics assignments in online learning to elementary school students. This research was conducted at SDN 104201 in Pond Village and was carried out in October 2021, carried out on fifth grade elementary school students and teachers. online is in difficulty in understanding which is caused because students are required to understand the material independently at home, difficulty accessing study material, difficulty in collecting assignments due to being constrained by an unstable internet network where if there is a power outage the internet network will be completely lost. This results in less student interest in learningand also causes a decrease in the value obtained by students. The decline experienced by studentsis not too significant, because students are still assisted by their parents in doing assignments, but there are still differences in learning outcomes obtained during face-to-face learning and onlinelearning.